Odpowiedź :
a) = x²+10y+25y²
b) = 9a²-6b/2+b²/4
c) = -(a²-√2b)² = -(a²-2√2b+2b²)= -a²+2√2b-2b²
d) = 4y²+4y√x+x
e) = 1/4a²-3b²
f) = -4/9a²-4a/9a+4a/9a+4a²/9= -4/9a²+4a²/9
b) = 9a²-6b/2+b²/4
c) = -(a²-√2b)² = -(a²-2√2b+2b²)= -a²+2√2b-2b²
d) = 4y²+4y√x+x
e) = 1/4a²-3b²
f) = -4/9a²-4a/9a+4a/9a+4a²/9= -4/9a²+4a²/9
a) x² + 25y²
b)9a² + 2b (pierwiastek i potęga druga się ukrucą więć zostanie 2)
c)a² + 2b²
d)4y² - x
e)1/4a +1/2a√3b + 1/2a√3b + 9b²
f)4/9a² + 4a/9a + 4a/9a + 4a²/9
b)9a² + 2b (pierwiastek i potęga druga się ukrucą więć zostanie 2)
c)a² + 2b²
d)4y² - x
e)1/4a +1/2a√3b + 1/2a√3b + 9b²
f)4/9a² + 4a/9a + 4a/9a + 4a²/9
a) x² + 25y²
b)9a² + 2b
c)a² + 2b²
d)4y² - x
e)1/4a +1/2a√3b + 1/2a√3b + 9b²
f)4/9a² + 4a/9a + 4a/9a + 4a²/9
powinno byc dobrze.
b)9a² + 2b
c)a² + 2b²
d)4y² - x
e)1/4a +1/2a√3b + 1/2a√3b + 9b²
f)4/9a² + 4a/9a + 4a/9a + 4a²/9
powinno byc dobrze.